VD_FINDINFO Jug / 2019 / 248 vom 24. Juni 2019 - VD Tribunal cantonal (2019)
JUGEMENT PAR DÉFAUT, NOTIFICATION DE LA DÉCISION, DOMICILE ÉLU, CONNAISSANCE, CONDITION DE RECEVABILITÉ | 368 al. 1 CPP (CH), 371 al. 1 CPP (CH), 403 al. 1 let. a CPP (CH), 85 CPP (CH), 87 CPP (CH)